Development of 3D Hologram Learning Media based on Holo-SDK for Multimeter Introduction - Dewi Patimah; Djuniadi Djuniadi (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
Through the growth of learning media, the application and development of 3D hologram technology have penetrated several industries, including education. Learning media from several studies have not been able to involve students effectively. This study aims to determine the development, feasibility, practicality, and effectiveness of the Holo-SDK for multimeter introduction learning media in Basic Electronics Engineering. The R&D method used the ADDIE development model (analysis, design, development, implementation, and evaluation) with a descriptive quantitative approach. The research instrument consisted of a questionnaire in the form of a validation and practicality instrument and a test in the form of an effectiveness instrument. The results show that 3D hologram media based on Holo-SDK is feasible, practical, and effective in improving student learning outcomes as indicated by the difference in test scores before and after using the media through the sample t-test and N-Gain test.